Nano-Impact Tests on Micro-Blasted Coatings for Assessing Their Brittleness - Bouzakis, Konstantinos-Dionysios; Gerardis, Stefanos; Skordaris, Georgios; Bouzakis, Emmanouil (International Conference on Plasma Surface Engineering, 2013)
Residual compressive stresses can be induced into a PVD film up to a certain depth from the coating surface via micro-blasting. Depending on the micro-blasting conditions, the deformed film depth varies, thus affecting the coatings performance in different applications. A method has been already introduced for determining mechanical strength properties gradation in coatings after micro-blasting.